The Impact Of Breastfeeding as a Compenion on Icrease Breastfeeding Self-Efficacy And Motherly Ability to Breastfeed - Shiddiqoh, Faizzatus (Universitas Aisyah Pringsewu, 2025)
Background: Breastfeeding is a natural process after a person gives birth. Not all mothers succeed in sucking well. Some mothers submitted reasons that stopped breastfeeding included a mother's confidence and a lack of information about the benefits and techniques of proper and correct nursing. It requires cooperation from all sides in achieving exclusive breastfeeding. Objective: To analyse the impact of breastfeeding on self efficacy and mother's ability to breastfeed.Methods: Research is a kind of experimental quasical research with a quantitative approach using Non Equivalent Control Group Design design. Sampling with a cluster random sampling technique with an intervention group of 25 respondents and a control group of 25. Given pre-test and post-test in each group as well as breastfeeding treatment for 6 weeks with 4 visits. The results were analyzed using paired t-test and independent t-tests.Results: There was an influence of breastfeeding on self-effectiveness and mother's ability to breastfeed both in the intervention and control groups (p=0,000), but there was a difference in the increase in the average self effectiveness score of 10.24 in intervention groups versus 5.28 in control groups. While in breastfeeding, there was an increase in the average breastfeed skill rating of 30.64 in the intervention group, compared to 25.40 in the control group. There was an average increase in knowledge level in the intervention group of 2.96 while in the control group of 1.52.Conclusion: Accompanying breastfeeding can increase breastfeeding self efficacy and mother's ability to breastfeed